Species-specific identification of collagen components in Colla corii asini using a nano-liquid chromatography tandem mass spectrometry proteomics approach - Li X (Dove Medical Press, 2017)
Xue Li,1 Feng Shi,2 Liping Gong,2 Baojian Hang,2 Daoyuan Li,1 Lianli Chi1 1National Glycoengineering Research Center, Shandong Provincial Key Laboratory of Carbohydrate Chemistry and Glycobiology, and State Key Laboratory of Microbial Technology, Shandong University, Jinan, Shandong, People’s Republic of China; 2Scientific Research Division, Shandong Institute for Food and Drug Control, Jinan, Shandong, People’s Republic of China Abstract: Colla corii asini (CCA) is a protein-based traditional Chinese medicine made from donkey skins. Because it has the ability to nourish blood, its demand is increasing rapidly. The shortage of donkey skins increases the risk of the adulteration of CCA products with other animal skins. To ensure the drug efficacy and safety of CCA products, a proteomics technique was applied to reveal proteins in the skins of donkey, horse, cattle, and pig. Species-specific peptides for each animal species were predicted using bioinformatics, and their presence in the skins and gelatin samples was examined by nano-liquid chromatography-tandem mass spectrometry (nano-LC-MS/MS). One unique marker peptide for each animal species was selected to develop an LC-MS/MS multiple reaction monitoring method. The capability of this method to identify donkey, horse, cattle, and pig materials was demonstrated by analyzing in-house-made donkey gelatins containing different amounts of other animal skins and commercial CCA products. The adulteration of non-donkey species could be sensitively detected at a low level of 0.5%. Hybrid animals, such as mules and hinnies, were also differentiated from donkeys. We provide a practical tool for the quality control of CCA products. The strategy can also be used to study other important traditional Chinese medicines which contain animal proteins. Keywords: Colla corii asini, collagen, proteomics, adulteration, mass spectrometry